Epitheliotropic cutaneous T-cell lymphoma associated with melanoma in a dog: case report - Palumbo, M. I. P. [UNESP]; Rossetto, V. J. V. [UNESP]; Torres Neto, R. [UNESP]; Brandão, C. V. S. [UNESP]; Amorim, R. L. [UNESP]; Fabris, V. E. [UNESP]; Machado, L. H. A. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
Several types of tumors affect dogs' skin. Simultaneously occurring neoplasms with different histological patterns might be rarely present in the same animal. This paper describes the occurrence of epitheliotropic cutaneous T-cell lymphoma and melanoma in a dog. The animal had nodular lesions in the abdominal region and serpiginous plaques on the dorsal region of the trunk. Cytology evidenced malignant fusiform cells from the abdominal lesions as well as few round cells from the dorsal. The histopathological examination of the abdominal lesions showed dermis with polygonal to spindle-shaped neoplastic cells. The lesion of the dorsal region evidenced neoplastic round cells with generally distinct cell borders and a moderate amount of eosinophilic cytoplasm. Abdominal lesions were positive for Melan A. Dorsal and forelimb lesions were positive for CD3. This study reports the occurrence of epitheliotropic cutaneous T-cell lymphoma and malignant melanoma in a crossbred Boxer dog and discusses the importance of performing immunohistochemical profile to confirm the phenotype of the tumor.

Diferentes tipos de tumores podem ocorrer na pele de cães. É rara, porém, a ocorrência simultânea de neoplasias com origens histológicas diferentes no mesmo animal. Este trabalho descreve a ocorrência de linfoma cutâneo epiteliotrópico de células T e melanoma em um cão. O animal apresentava lesões nodulares na região abdominal e placas serpiginosas na região dorsal do tronco e membros. A citologia evidenciou células fusiformes malignas das lesões abdominais, bem como algumas células redondas nas dorsais. O exame histopatológico das lesões abdominais mostrou derme com células neoplásicas poligonais a fusiformes. A lesão da região dorsal evidenciou células redondas neoplásicas com citoplasma eosinofílico. Lesões abdominais foram positivas para Melan A. Lesões dorsais e de membros anteriores foram positivas para CD3. Este estudo relata a ocorrência de linfoma cutâneo de células T epitheliotropic e melanoma maligno em um cachorro Boxer, e discute a importância da realização de perfil imuno-histoquímico para confirmar o fenótipo do tumor. A importância do perfil imuno-histoquímico para confirmar o tipo de neoplasia também é discutida.
Linfoma cutâneo epiteliotrópico de células T associado a melanoma em cão: relato de caso
Keywords: Oncology; Immunohistochemistry; Malignant skin neoplasms; Oncologia; Imunohistomquímica; Neoplasias cutâneas malignas